Heat Loss and Cost Reduction of Insulation Materials on Geothermal Pipes - Ristiyan Ragil Putradianto; Allen Haryanto Lukmana (Journal of Petroleum and Geothermal Technology, 2023)
Power plant in X field has 6 production wells with steam dominated reservoir type. Fluid flowing in pipe from the well to the plant experienced heat loss that occured due to difference in the temperature of the flowing steam and the outside that caused heat transfer from inside the pipe to the outside. Minimizing heat transfer can be done by using an insulator is installed on the outside of the pipe, in this case, Foamglas W+F Insulation Â The method to assess the heat loss is by calculating material properties as well as fluid properties to deterimine heat transfer rate for one well as representation of all wells. From the calculation, it can be concurred that the use of Foamglas W+F Insulation material provides reduction in heat loss of 113,61 kWh for one well with significant reduction in costs of 1.035 billion IDR per well per year. By comparing the heat loss reduction value which is almost the same, the option to replace the materials to Foamglas W+F insulation material is cheaper than adding the existing insulation thickness.